2017
DOI: 10.3390/s17081807
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Nonenzymatic Glucose Biosensor Based on the Regulatory Effect of Glucose on Electrochemical Behaviors of Colloidal Silver Nanoparticles on MoS2

Abstract: A novel and highly sensitive nonenzymatic glucose biosensor was developed by nucleating colloidal silver nanoparticles (AgNPs) on MoS2. The facile fabrication method, high reproducibility (97.5%) and stability indicates a promising capability for large-scale manufacturing. Additionally, the excellent sensitivity (9044.6 μA·mM−1·cm−2), low detection limit (0.03 μM), appropriate linear range of 0.1–1000 μM, and high selectivity suggests that this biosensor has a great potential to be applied for noninvasive gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…However, PNA‐Ag nanocomposites exhibit large anodic and cathodic currents, which are attributed to better electrochemical activity because of the presence of AgNPs and larger electrochemical surface area provided by the nanocomposites. Comparison of CV plots of PNA‐Ag systems with previous reports reveals that all characteristic peaks of silver, which correspond to the electrooxidation and electroreduction of incorporated metallic silver, were observed during the potential scan, and electrochemical transitions are assigned accordingly . The electrochemical transitions at the PNA‐Ag‐modified CPE surface are represented in the eqns.1‐4.…”
Section: Resultsmentioning
confidence: 74%
“…However, PNA‐Ag nanocomposites exhibit large anodic and cathodic currents, which are attributed to better electrochemical activity because of the presence of AgNPs and larger electrochemical surface area provided by the nanocomposites. Comparison of CV plots of PNA‐Ag systems with previous reports reveals that all characteristic peaks of silver, which correspond to the electrooxidation and electroreduction of incorporated metallic silver, were observed during the potential scan, and electrochemical transitions are assigned accordingly . The electrochemical transitions at the PNA‐Ag‐modified CPE surface are represented in the eqns.1‐4.…”
Section: Resultsmentioning
confidence: 74%
“…Fabricating highly porous nanofibres using electrospinning and combining them with a bioreceptor is an example of this method for enhancing sensor sensitivity, sensing range and bioreceptor immobilization [64]. Likewise, conductive metal nanoparticles can be used to enhance the performance of non-conductive but highly selective materials [65,66].…”
Section: Sensor Manufacturing Methodsmentioning
confidence: 99%
“…Non-conductive materials with desirable properties such as high selectivity, mechanical strength and flexibility, biocompatibility and large surface areas can still be used in electrode fabrication by doping with conductive materials. Anderson et al [65] presented this as a useful method in non-enzymatic amperometric glucose sensing, where an intrinsically non-conductive material, molybdenum disulphide (MoS 2 ), was nucleated with silver nanoparticles and used to modify a glassy carbon electrode. The LoD was found to be 0.03 µM with a sensitivity of 9044.6 µA mM −1 cm 2 and a linear range of 0.1-1.0 mM of glucose concentration, with high selectivity towards glucose detection.…”
Section: Methodsmentioning
confidence: 99%
“…A negligible 3.4% reduction in the response of the sensor was measured after ambient storage for 4 weeks. In addition, Anderson et al reported a highly sensitive non-enzymatic glucose biosensor by incorporating colloidal silver nanoparticles with MoS 2 [28]. The introduction of Ag nanoparticles was to address the intrinsic poor conductivity of MoS 2 .…”
Section: Electrochemical Glucose Biosensor-based Mos 2 Nanocompositesmentioning
confidence: 99%